Correction: Supported C60-IL-PdNPs as extremely active nanocatalysts for C–C cross-coupling reactions. Issue 15 (31st March 2017) - Giacalone, Francesco; Campisciano, Vincenzo; Calabrese, Carla; La Parola, Valeria; Liotta, Leonarda F.; Aprile, Carmela; Gruttadauria, Michelangelo
Abstract : Correction for 'Supported C60 -IL-PdNPs as extremely active nanocatalysts for C–C cross-coupling reactions' by Francesco Giacalone et al., J. Mater. Chem. A, 2016, 4, 17193–17206.